First description of the genus Hyalella Smith, 1874 (Crustacea, Amphipoda, Hyalellidae) for the state of Mato Grosso and the Central-Western region of Brazil - Sobral, Cecilia Silva Ribeiro; Nascimento, Amanda De Serpa; Marçal, Sandra Francisca; Bueno, Alessandra Angélica De Pádua (Zootaxa, 2026)
This study describes the first species of Hyalella from the state of Mato Grosso, Central-West Brazil, based on material collected from the Salobra Stream (Córrego Salobra) at Recanto Ecológico da Lagoa Azul, Bom Jardim District, Nobres, Mato Grosso. Hyalella nobrensis sp. nov. is characterized by the presence of three serrate setae of a new type with an accessory seta on the inner face of the propodus of gnathopod 1, the absence of a curved seta on the inner ramus of uropod 1, simple setae on the inner margin of maxilla 2, one plumose seta on the dactylus of gnathopods 1 and 2, and a telson apically rounded with two cuspidate setae and four lateral plumose setae. This study raises the number of described Hyalella species in Brazil to 52 and expands our understanding of Hyalella diversity in additional regions of this continental-scale country.